The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
DOI: 10.14264/uql.2015.929
|View full text |Cite
|
Sign up to set email alerts
|

SME performance: the role of networking, innovation breadth, and business model design

Abstract: Because small and medium-sized enterprises (SMEs) are pivotal to the health and vibrancy of economies, it is crucial for researchers to understand the factors that significantly underlie SME performance. Two of the most widely identified antecedents to SME performance are innovation and networking. However, despite widespread attention, the theoretical and empirical status of the relationships between innovation, networks and SME performance remain uncertain. Some researchers note that claims regarding a direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 460 publications
(794 reference statements)
2
7
0
Order By: Relevance
“…The data presented in Figure 2 show that France takes the lead in terms of business-to-business collaboration as more than 50 per cent of innovative firms have co-created goods or services in the year 2018. Our results are consistent with prior Australian studies and government reports that highlight a low level of collaboration in small and medium-sized firms (Gronum 2015;Australian Government 2017;Innovation and Science Australia 2017).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The data presented in Figure 2 show that France takes the lead in terms of business-to-business collaboration as more than 50 per cent of innovative firms have co-created goods or services in the year 2018. Our results are consistent with prior Australian studies and government reports that highlight a low level of collaboration in small and medium-sized firms (Gronum 2015;Australian Government 2017;Innovation and Science Australia 2017).…”
Section: Resultssupporting
confidence: 92%
“…It has no effect on growth for the low or average growth firms. Consequently, the relationship between innovation diversity and growth is highly contextual (Gronum 2015). The modest growth effect of innovation in this study can be explained on the grounds that the majority of the firms in our dataset are non‐employing or microfirms (around 50 per cent as in Appendix ), and such firms may lack the capacity to transform their innovation into commercial success.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Careful and informed choice is made in selecting these particular capabilities. Studies affirm that networking and innovation are two of the most widely identified antecedents to SME performance [6]. Dynamic capabilities literature [7] also attests to the fact that sensing capability is "more significant than ever to SMEs" (p. 3).…”
Section: Introductionmentioning
confidence: 99%